Occupational Allergies in Dentistry: A Cross-Sectional Study in a Group of French Dentists - Lise Boudinar; Damien Offner; Sophie Jung (MDPI AG, 2021)
Background: Dentists have a high risk of developing occupational allergies due to their repeated exposure to many professional allergens. The aim of this cross-sectional study was to assess occupation-related allergies in a group of French dentists and to determine the main associated risk factors. Methods: A self-administered questionnaire about allergies, particularly occupational allergies, was published online in a private group dedicated to French dentists. Results: Data from 584 French dentists were collected; 50.3% of the respondents presented allergies and 13.4% presented occupation-related allergies. Regarding professional allergens, natural rubber latex, cleaning products, and resins were the most frequently incriminated substances. Temporary interruption of activity was reported by 10.3% of individuals suffering from occupational allergies. Almost 65% of them used different reliever medications for the management of acute exacerbations, but maintenance treatment was implemented in only 34.6% of cases. Having a general allergy was the first predictor of occupational allergies with an odds ratio of 7.49. Conclusions: The frequency and the impact of occupational allergies were significant among our study population of French dentists, particularly in those with an associated allergic background. Education and prevention programs are key measures to minimize risk.